Advances in sensing mechanisms and micro/nanostructured sensing layers for surface acoustic wave-based gas sensors. Issue 17 (14th April 2023) - Li, Xue; Sun, Wenfeng; Fu, Wei; Lv, Haifeng; Zu, Xiaotao; Guo, Yuanjun; Gibson, Des; Fu, Yong-Qing
Abstract : Surface acoustic wave (SAW) technology has been extensively used in communications and sensing applications. This review summarizes the recent advancement of micro- and nanostructured sensing materials in enhancing the gas sensing performance of SAW devices. Abstract : Surface acoustic wave (SAW) technology has been extensively used in communications and sensing applications. For SAW based gas sensing applications, the sensitive material or sensing layer which is coated onto the SAW sensor is vital for its sensitivity, selectivity, limit of detection, and repeatability, as changes of sensing signals (including frequency, amplitude, and phase angle) are strongly linked to variations of mass loading, electrical conductivity and elastic modulus (or elastic loading) of this sensing layer. There have been rapid developments in this field recently but great challenges still remain in the choices of suitable sensing materials, structures and mechanisms of these sensing layers. This paper reviews recent advances of micro- and nanostructured sensing materials and their selection, their sensing mechanisms and designs towards enhancing the gas sensing performance of SAW devices. We first discuss different sensing mechanisms based on SAW principles, along with the key sensing influencing parameters. We then highlight and categorize recently reported gas sensing materials into semiconductor metal oxides, carbon-based materials and polymers. We further focus the discussion on the relationships among the micro/nanostructures, compositions, and structure-sensing performance of the SAW based sensors. Finally, we highlight key challenges and potential solutions as well as future directions of sensing materials for SAW based gas sensors.